2009
DOI: 10.1111/j.1751-7893.2009.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Comprehensive Assessment of At‐Risk Mental States (CAARMS) to the Japanese population: reliability and validity of the Japanese version of the CAARMS

Abstract: The CAARMS-J is a reliable and valid tool for assessing and detecting ARMS in Japanese clinical settings, suggesting that the concept of ARMS is applicable in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 34 publications
7
33
0
Order By: Relevance
“…The ARMS group was assessed using the Japanese version of the Comprehensive Assessment of At-Risk Mental States (CAARMS-J; Miyakoshi et al, 2009), and diagnosis was confirmed by the clinical team. Participants had no history of DSM-IV psychotic disorders and met one or more of the following criteria for ARMS developed by the Personal Assessment and Crisis Evaluation (PACE) Clinic in Melbourne, Australia (Yung et al, 2004).…”
Section: Participantsmentioning
confidence: 99%
“…The ARMS group was assessed using the Japanese version of the Comprehensive Assessment of At-Risk Mental States (CAARMS-J; Miyakoshi et al, 2009), and diagnosis was confirmed by the clinical team. Participants had no history of DSM-IV psychotic disorders and met one or more of the following criteria for ARMS developed by the Personal Assessment and Crisis Evaluation (PACE) Clinic in Melbourne, Australia (Yung et al, 2004).…”
Section: Participantsmentioning
confidence: 99%
“…All participants provided written informed consent, or if subjects were aged <18 year, their parents provided written informed consent while the participant provided written assent. Inclusion criteria were (1) aged 14 to 35 years, (2) exhibited ARMS criteria using the Comprehensive Assessment of ARMS (CAARMS; Miyakoshi, Matsumoto, Ito, Ohmuro, & Matsuoka, ; Yung et al, ) and met the attenuated psychosis group criterion, (3) exhibited an impairment in social functioning (GAF score ≤ 50, and/or a reduction by 30% on the GAF for at least 1 month in the past year), (4) native Japanese speaker, (5) outpatient. Exclusion criteria were (1) present or past diagnosis of psychosis, (2) use of antipsychotic medication within the last month or cumulative dose of antipsychotic medication greater than 30 mg of haloperidol‐equivalent within the last 6 months, (3) present alcohol or drug abuse, (4) serious risk of suicide or violence, (5) known intellectual disability (IQ < 70) or severe learning disorder, (6) presence of organic brain disorder.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome was the total score on the Positive and Negative Syndrome Scale (PANSS; Kay, Fiszbein, & Opler, ) and secondary outcomes included PANSS subscale scores and positive symptoms by the CAARMS (Miyakoshi et al, ; Yung et al, ). We also measured clinical variables using the Beck Depression Inventory‐II (BDI‐II; Beck, Steer, & Brown, ), the State‐Trait Anxiety Inventory‐Form JYZ (STAI; Hidano, Fukuhara, Iwawaki, Soga, & Spielberger, ), the Global Assessment of Functioning (GAF; Hall, ), the World Health Organization Quality of Life scale (WHO‐QOL26; The‐WHOQOL‐Group, ), the Client Satisfaction Questionnaire (CSQ; Larsen, Attkisson, Hargreaves, & Nguyen, ) and risk of suicidality and aggressive behaviour items of the CAARMS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also reported good ability for the CAARMS scores to discriminate between young people deemed at risk of impending psychosis and a control group recruited from a local unemployment centre. Versions of the CAARMS in Italian (Fusar‐Poli, Hobson, Raduelli, & Balottin, ) and Japanese (Miyakoshi, Matsumoto, Ito, Ohmuro, & Matsuoka, ) have also been validated.…”
Section: The Comprehensive Assessment For At‐risk Mental States (Caarms)mentioning
confidence: 99%